Estudio de factibilidad para el desarrollo de un sistema de gestión empresarial para el Minimarket Elsi ubicado en el cantón Jaramijo - Macias Velez, Ingrid Belen (2021)
This study takes into consideration the feasibility of creating a Business Management System for the company called "Minimarket Elsi" which is located in the Jaramijo city because among the objectives of said company is its growth and expansion, but the information records that are managed are manually, that is, it does not have a system that allows it to automate processes, record and use the information they produce to improve decision-making, in addition to avoiding problems such as data inconsistency and poor organization. As the economy is the line in which most of the activities of society are developed, a large number of companies currently make use of different systems that allow them to improve their services and activities both within their facilities and for the use of customers by providing a better attention, carrying out their activities in less time and achieving an increase in their sales, so that companies that for different reasons prefer not to make use of current computer tools run the risk of being left behind by the consumer population, so the case study seeks to avoid such risks considering the viability of using a Business Management System tailored to the existing needs of the company allowing said software to make use of the registered information to be able to know the current performance of the company, for this it was used descriptive research together with analytical and qualitative methods to observe the causes and effects of the problem by adding the techniques of observation and interview with the owner of the minimarket for the collection of important information necessary for the work carried out and thus be able to know the activities of the company and its needs, which allows work tailored to the same.